Analysis of the Application of Spatial Audio in VR Tower Defense Game Rise of Majapahit in Improving Better Sound Localization Ability - (:unkn) unknown (My University, 2024)
Virtual reality is a technology that is commonly used in games. To enhance its immersiveness, spatial audio plays a very important role as it can allow players to feel very important as it allows the player to feel the depth and direction of sounds in the game environment. The number of players who still find it difficult to localize the presence of enemies that are visually out of visual sight, making it a little difficult for them to complete the game. This research examines application of spatial audio in the VR game Tower Defense: Rise of Majapahit to improve sound localization capabilities. Using comparative quantitative methodology, this study tested respondents in physical and virtual environments, collecting data through t-tests. in physical and virtual environments, collecting data through independent t-test. Results showed a significant difference in ability to identify the direction of sound, easier virtually than physically, particularly sounds from behind, right, and left. This finding confirms the importance of spatial optimization of audio in VR games to create a more immersive gaming experience. VR games to create a more immersive and realistic gaming experience and realistic play experience. This research provides insights for further development of spatial audio technology, supporting the creation of immersive and satisfying virtual environments for the player.
Keywords: SOCIAL SCIENCES::Statistics, computer and systems science::Informatics, computer and systems science::Information technology; TECHNOLOGY